PENGAPLIKASIAN ASAS SEDERHANA, CEPAT DAN BIAYA RINGAN DALAM PENGGUNAAN SISTEM PERSIDANGAN SECARA ELEKTRONIK (E-COURT) OLEH ADVOKAT DAN HAKIM DI PENGADILAN NEGERI PADANG - Suharizal; Suhelmi Helia (Halu Oleo University, 2024)
This research aims to find out what factors are taken into consideration by human resources, especially judges and advocates, when conducting electronic hearings via e-court or conventional hearings and to find out what the weaknesses are in holding electronic hearings. The research was conducted at the Padang District Court with the research population being judges and advocates. The sample was taken using a purposive sampling method, so that 4 judges and 3 advocates were obtained as research samples. Data was collected through observation and interviews with informants. The research results show that there are several factors that are taken into consideration by human resources, especially judges and lawyers, in deciding whether to conduct conventional trials or electronic trials, namely in terms of efficiency and flexibility in time, costs and transparency of the judicial process. In applying the principle of simple, fast and low cost in using the electronic court system (e-court), there are several factors that are weaknesses of e-court, namely Human Resources who are not fully ready and accustomed to using technology and weaknesses of the e-court system itself, such as the existing system. loading is still frequent, case transmission calculations are not correct, and the device is not optimal.